Intrathecal activation of CD8+ memory T cells in IgG4‐related disease of the brain parenchyma. Issue 8 (13th July 2021) - Friedrich, Mirco; Kehl, Niklas; Engelke, Niko; Kraus, Josephine; Lindner, Katharina; Münch, Philipp; Mildenberger, Iris; Groden, Christoph; Gass, Achim; Etminan, Nima; Fatar, Marc; von Deimling, Andreas; et al.
Abstract: IgG4‐related disease (IgG4‐RD) is a fibroinflammatory disorder signified by aberrant infiltration of IgG4‐restricted plasma cells into a variety of organs. Clinical presentation is heterogeneous, and pathophysiological mechanisms of IgG4‐RD remain elusive. There are very few cases of IgG4‐RD with isolated central nervous system manifestation. By leveraging single‐cell sequencing of the cerebrospinal fluid (CSF) of a patient with an inflammatory intracranial pseudotumor, we provide novel insights into the immunopathophysiology of IgG4‐RD. Our data illustrate an IgG4‐RD‐associated polyclonal T‐cell response in the CSF and an oligoclonal T‐cell response in the parenchymal lesions, the latter being the result of a multifaceted cell–cell interaction between immune cell subsets and pathogenic B cells. We demonstrate that CD8 + T effector memory cells might drive and sustain autoimmunity via macrophage migration inhibitory factor (MIF)‐CD74 signaling to immature B cells and CC‐chemokine ligand 5 (CCL5)‐mediated recruitment of cytotoxic CD4 + T cells. These findings highlight the central role of T cells in sustaining IgG4‐RD and open novel avenues for targeted therapies. SYNOPSIS: This translational study demonstrates the potential of single‐cell profiling technologies to support clinicians in the diagnosis of rare autoimmune disorders while shedding new light into potential molecular pathomechanisms of intercellular communication in IgG4‐related disease. T‐cell ‐ T‐cell crosstalk facilitates recruitment of helper and cytotoxic CD4 + T‐cells to manifestation sites of IgG4‐related disease. T‐cell‐derived CXCL13 might regulate pathogenic B cell migration into the CNS and promote intrathecal accumulation of B‐cells. Recurrent IgG4‐RD in three intracranial manifestation sites is driven by a clonal T‐cell response. Abstract : This translational study demonstrates the potential of single‐cell profiling technologies to support clinicians in the diagnosis of rare autoimmune disorders while shedding new light into potential molecular pathomechanisms of intercellular communication in IgG4‐related disease.